2014
DOI: 10.2139/ssrn.2557342
|View full text |Cite
|
Sign up to set email alerts
|

Open Data in the Governance of South African Higher Education

Abstract: CHE G o v r n m e nt cou ncils an d a g e n c ie s CREST DataFirst/UCT 23 public universities P 1 P ub lic universi tie s CHET N o n -G o ve rnm ental Org an is a ti o n s CHEC African Knowledge Base HIV Prevalence Survey Higher Education Data Analyser International state-funded donor agencies DFID, USAID, Danida, IDRC, Sida, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recent literature suggests that there are growing demands from the public side (e.g. general citizens, community organizations) to utilize civic data for community development (Gurstein, 2011; The United Nations Secretary-General’s Independent Expert Advisory Group on a Data Revolution for Sustainable Development (IEAG), 2014; van Schalkwyk et al , 2014). Public libraries should anticipate these future needs and could be more active players in supporting public demand for data through their curation services.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature suggests that there are growing demands from the public side (e.g. general citizens, community organizations) to utilize civic data for community development (Gurstein, 2011; The United Nations Secretary-General’s Independent Expert Advisory Group on a Data Revolution for Sustainable Development (IEAG), 2014; van Schalkwyk et al , 2014). Public libraries should anticipate these future needs and could be more active players in supporting public demand for data through their curation services.…”
Section: Discussionmentioning
confidence: 99%
“…As such, Van Schalkwyk et al (2014) the current existing copyright policies in government and public-funded entities are against the notion of opening data for public and commercial use (Eyal, 2013).…”
Section: Promotion Of Access To Information Act ("Paia") No 2 Of 2000mentioning
confidence: 99%
“…In the context of open data, Van Schalkwyk, Willmers, and Czerniewicz (2014) reported that data intermediaries play several possible roles, such as increasing data accessibility and utility, serving as "keystone species" in data ecosystems, and democratizing the impacts and use of open data. Several other studies have echoed the potential and significance of intermediaries in the contexts of government data (Chattapadhyay, 2014), developing countries (Davies, 2014;Van Schalkwyk et al, 2014), and broadly in ICT (Diaz Andrade, & Urquhart, 2010) and demonstrated intermediaries' crucial role in linking different agents in open data supply chains, including grassroots communities (Van Schalkwyk et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%